Chemically tailored molecular surface modification of cellulose nanofibrils for manipulating the charge density of triboelectric nanogenerators. (November 2021) - Liu, Yanhua; Fu, Qiu; Mo, Jilong; Lu, Yanxu; Cai, Chenchen; Luo, Bin; Nie, Shuangxi
Abstract: Studying the surface chemical composition of materials is greatly significant to further understand the triboelectric charge generated during contact electrification. Although it has been studied to modify material surfaces by chemical methods to change the charge density, understanding the effect more systematically has not been elucidated in detail. In this work, silane coupling agents with the same main chain but different terminal functional groups were selected to chemically tailor cellulose nanofibrils. The results show that surface charge density of a material can be altered by introducing functional groups with different electron-withdrawing or electron-donating abilities to its surface. By regulating the number and density of the functional groups, the range of the charge density can be tailored more specifically. More importantly, a relatively systematic and improved mechanism is proposed to clarify the influence of chemically tailored surfaces on contact electrification. This article provides guidance for the systematic study of chemically tailored molecular surface modification to control triboelectric charge density. Graphical Abstract: ga1 Highlights: Silane coupling agents were selected to tailor cellulose nanofibrils for manipulating the charge density. Charge density can be altered by introducing functional groups with electron-withdrawing or electron-donating abilities. Regulating the number and density of functional groups can tailor the range of the charge density more specifically.